Broadcast/cable/web programming : strategies and practices - Eastman, Susan Tyler (Beijing, China : Peking University Press, 2001)
A more formal statement of the theory and model guiding the authors thinking has been added to the first chapter, accompanied by basic descriptive information about the industry and about the viewing process to better meet the needs of teachers.
Part1. Programming Resources and Constraints -- Part2. Broadcast Television Strategies -- Part3. Cable, Satellite and Online Strategies -- Part4. Radio Programming
Includes bibliographical references and index.
Keywords: TELEVISION PROGRAMS -- PLANNING